Bio-resources and Environmental Status in Narara and Poshitra Islands at Marine National Park, Gulf of Kachchh, Gujarat - Joshi, Arti; Desai, A. Y.; Bhatt, A. J.; Dave, T. H. (International Journal of Bio-resource and Stress Management, 2018)
Gujarat covers a total coastline of 1600 km, which is the longest among all the littoral states of country and is 21.9% of the Indian coastline (7517 km). The coastline has two indentations, the Gulf of Khambhat and Kachchh; both together cover around 60% of total coastline of Gujarat. The present MNP is also known for its rich species diversity viz., as more than 49 species of hard corals, 23 species of soft corals, 70 species of sponges, 421 species of fishes, 27 species of prawns, 30 species of crabs, 199 species of mollusk, 16 species of echinoderms, 172 species of birds, 3 species of sea mammals, 6 species of mangroves, 3 species of sea turtle, 108 species of brown, green and red algae, etc. This rich diversity necessitates the study on the present status of coastal bio-resource potential not only on the basis of physical-chemical, biological and ecological but also through cultural, economic and social development point of view of MNP (GoK). The aim of the present status report is to identify the important bio-resources and their present environmental status in Narara and Poshitra islands of Gulf of Kachchh, Gujarat. This identified resources and their present status can be useful to monitor it through the long-term study with observations on regular intervals as well as to analyses the pressure on the bio-resources and for implementation of their management policies, if any concern for future generation.